Effect of Supplementation of Aloe Vera Juice on Growth Performance of Japanese Quails - P., Jogeswar; D, Sreekumar; P, Ponnuvel; P.K., Mandal; R, Ganesan; N, Elanchezhiyan (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
An experiment was carried out in 300 Namakkal strain of Japanese quails from day-old to five weeks of age to study the effect ofsupplementation of Aloe vera (Aloe barbadensis) juice at different concentrations through drinking water on growth performance.The birds were divided into four treatment groups with three replicates in each treatment and each replicate had 25 birds. The four experimental groups consisted of T0 (control), T1, T2 and T3 supplemented with Aloe vera juice @ 0, 1.0, 1.5 and 2.0%, respectively, in drinking water. The body weight of quails was measured weekly from hatch till five weeks of age and feed consumption and feed conversion ratio were calculated weekly. Mortality and livability were recorded daily and weekly, respectively. The results revealed a significant difference (p
Keywords: Aloe vera, Body weight; Feed conversion ratio; Growth performance, Japanese quail.